Pengaruh Kompensasi dan Dukungan Organisasi terhadap Kinerja Pegawai pada Kantor Imigrasi Kelas III Non TPI Bima - Fahrizal Fahmi; Muhammad Yusuf (Universitas Bumigora, 2022)
The effect of compensation and organizational support on employee performance at the immigration office class III non TPI bima. This study aims to analyze the effect of compensation and organizational support on employee performance at the immigration office class III non TPI bima. This type of research used is associative research. The focus of this research includes whether compensation and organizational support affect employee performance. This study uses purposive sampling. Used a sample of 30 civil servants in the immigration office class III non TPI bima. The data of this study were obtained from questionnaires. The result of the multiple linear regression obtained Y=0,336 + 0,480 X1 + 0,506 X2. These result indicate that compensation and organizational support have an effect on employee performance at the class III immigration office non TPI bima.